Venous anastomosis procedure for treatment of lymphatic malformation in Klippel-Trenaunay syndrome - Motoi Kato, M.D; Shoji Watanabe, M.D. PhD; Takuya Iida, M.D. PhD; Azusa Watanabe, M.D. PhD (Elsevier, 2017)
Klippel-Trenaunay syndrome (KTS) is a congenital vascular anomaly in children, which requires treatment but challenging. The characteristics of KTS include disproportionality of the affected limbs, usually with enlargement due to lymphatic malformation (LM) [1]. Sometimes the condition is accompanied by pain that is difficult to treat. Compression therapy is one option for reducing the swelling; however, this has limitations [2]. We previously reported that lymphatic venous anastomosis (LVA) may be a safe and effective procedure for reducing the size of micro cystic type LM by decreasing the intra cystic lymph [3]. We treated a case of KTS in a 9-year-old boy who had improvement of lower abdominal swelling and penile pain after a single LVA. The method involved is to make a bypass, from the afferent lymph-collecting vessel to subcutaneous veins. However, to apply LVA to LM, it is sometimes problematic to detect the afferent flow in combined vascular malformations, such as KTS. Therefore, we performed VA making a bypass directly from LM, instead. We classify two types of LVA methods for LM: afferent lymph vessel LMVA (A-LMVA), and sidewall LMVA (S-LMVA). S-LMVA has more merits than the previously reported A-LMVA.